Thousands of Novel Endolysins Discovered in Uncultured Phage Genomes - Fernández-Ruiz, Iris; Coutinho, Felipe H.; Rodriguez-Valera, Francisco (Frontiers in Microbiology, 2018)
Bacteriophages express endolysins towards the end of their replication cycle to degrade the microbial cell wall from within, allowing viral progeny to be released. Endolysins can also degrade the prokaryotic cell wall from the outside, thus have potential to be used for biotechnological and medical purposes. Multiple endolysins have been identified within the genomes of isolated phages, but their diversity in uncultured phages has been overlooked. We used a bioinformatics pipeline to identify novel endolysins from nearly 200,000 uncultured viruses. We report the discovery of 2,628 putative endolysins, many of which displayed novel domain architectures. In addition, several of the identified proteins are predicted to be active against genera that include pathogenic bacteria. These discoveries enhance the diversity of known endolysins and are a stepping stone for developing medical and biotechnological applications that rely on bacteriophages, the most diverse biological entities on Earth.